BACOPA MONNIERA -A FUTURE PERSPECTIVE (International Journal of Pharmaceutical Sciences and Drug Research, 2009)
Bacopa moniera, a traditional Ayurvedic plant, used for centuries as a memory enhancing, anti-inflammatory, analgesic, antipyretic, sedative and antiepileptic agent. The plant, extract and isolated bacosides (the major active principles) have been extensively investigated in several laboratories for their different biological activities. In addition researchers have evaluated the anti-inflammatory, cardio tonic and other pharmacological effects of Bacopa monniera preparations/exracts. Therefore, in view of the important activities performed by this plant, research is an on going process over Bacopa monniera.